2016
DOI: 10.1002/acn3.291
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cryptogenic stroke in cancer patients

Abstract: ObjectiveTo clarify the characteristics of cryptogenic stroke in patients with active cancer.MethodsPatients with or without cancer diagnosed with acute ischemic stroke between January 2006 and February 2015 were extracted from a prospectively collected stroke database of Osaka University Hospital. Patients were categorized according to the presence of active cancer and known stroke mechanisms.ResultsAmong 1191 patients with acute ischemic stroke, 145 (12%) had active cancer. Patients with active cancer were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 18 publications
(23 reference statements)
2
46
2
3
Order By: Relevance
“…Similar findings with regard to blood coagulation factors and aetiology have also been shown [6, 8, 13, 27, 28], but as of yet, there is no score in place predicting active cancer in stroke patients. Based on our findings we constructed a predictive score for clinical use in order to detect ischaemic stroke patients with concomitant active cancer.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar findings with regard to blood coagulation factors and aetiology have also been shown [6, 8, 13, 27, 28], but as of yet, there is no score in place predicting active cancer in stroke patients. Based on our findings we constructed a predictive score for clinical use in order to detect ischaemic stroke patients with concomitant active cancer.…”
Section: Discussionsupporting
confidence: 61%
“…The proportion of stroke patients with active or occult cancer is debated and study findings reveal a value ranging from <2 to 13% [12, 27-29]. However, with increasing age of populations and thereby higher incidence of both stroke and cancer, uncovering cancer-associated strokes is becoming increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high plasma D-dimer levels and lesions in multiple vascular regions in patients with cryptogenic stroke independently predicted the presence of occult cancer. These findings suggest that the clinical features reported in cancer patients with cryptogenic stroke [9][10][11] appear to be useful for the identification of occult cancer in these patients. Similarly, these results confirm our hypothesis that plasma D-dimer levels and lesions in multiple vascular regions are useful to predict the presence of occult cancer as an Data are presented as median (interquartile range) or percentage (number).…”
Section: Discussionmentioning
confidence: 91%
“…30, 31 These cancer-related cryptogenic strokes tend to be associated with high D-dimer levels, infarctions in multiple vascular territories, and metastatic disease. 32, 54, 55 One common theory is that many cryptogenic strokes in cancer patients are from cardioembolic manifestations of cancer-mediated hypercoagulability, specifically nonbacterial thrombotic endocarditis, which comprises sterile, platelet-fibrin vegetations on cardiac valves. 31 Supporting this hypothesis is an older, highly-cited autopsy study of 256 cancer patients with cerebrovascular disease, which reported that nonbacterial thrombotic endocarditis was the leading cause of symptomatic ischemic stroke in this population.…”
Section: Cerebrovascular Pathophysiologymentioning
confidence: 99%